Validity for General Type Model Based on Fujimmon Growth Curve - Fujii, Katsunori (British Journal of Healthcare and Medical Research, 2022)
Fujimmon’s growth curve was proposed by Fujii[1], but unlike Scammon’s growth curve, three growth patterns were set. Moreover, Scammon’s growth curve was drawn freehand, but Fujimmon’s growth curve is drawn by a wavelet interpolation model. The growth curve for each type is clearly independent, but no essential classification criteria were discussed. Here an attempt is made to examine indicators that could be classification criteria for the general growth type, from the fact that among human attributes many internal organs are classified as having the general growth pattern. The wavelet interpolation model was applied to the growth distance values for attributes classified as the general growth pattern, for example internal organs and morphological elements, and the maximum peak velocity (MPV) was derived from the described growth velocity curve. With the ability to calculate the MPV, it was demonstrated that the growth distance curves of various attributes show a sigmoid curve. The age at MPV was then compared between several organs that showed sigmoid curves, and the variability between different sexes and in the same sex was investigated. The results for differences between the sexes showed a trend for later age at MPV in various organs in girls. A relationship between the level of maturity and the variability in the age at MPV in people of the same sex may be suggested.